Acquisition of Digital Evidence in Online Scam Cases (CyberCrime) on Whatsapp Chat Application Using NIST Method - Atmaja, Gede Agus Surya; Mogi, I Komang Ari (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
Cybercrime usually happen on internet. There are many type of cybercrime such as Cyberbullying, Online Scams, Malware etc. Whatsapp is a chatting application that is easy to use and many of its users. Because of many users that used whatsapp chatting application not infrequently many crimes occur there. Especially Online Scams, the perpetrator usually sell something online and make their target use whatsapp to contact them and their transaction begin there. In this research, we try to acquisition the smartphone data, exctract the whatsapp application from there, decrypt the database and view the message from there in case there are deleted message that can recovered.